Manajemen Mutu Pembelajaran Pendidikan Agama Islam (Tarbiyah) di Pondok Pesantren Bina Umat - Yahya Khunaifi (FAI, 2017)
Manajemen Mutu Pembelajaran Pendidikan Agama Islam (Tarbiyah) di Pondok Pesantren Bina Umat